Xyn-converter used in isolated two-phase three-wire AC power grids - João Henrique de Oliveira (2024)
Isolated electric AC power grids are feasible solutions to energize remote communities, usually based on renewables and energy storage devices, interfaced by power electronics converters that require high reliability. The key element of such a system is the grid-forming converter that provides the voltage magnitude and frequency to other devices, such as loads. Therefore, this dissertation proposes the two-phase three-wire (2Φ3W) xyn-converter applied in a case study of isolated riverside communities in the Brazilian Amazon region. This dissertation compares the current stresses of grid-forming converters (GFC) under an isolated grid mission profile, considering three different grid configurations in terms of the displacement angle between the voltage in the phases: 90◦ (αβn-GFC); 120◦ (abn-GFC) and 180◦ (xyn-GFC). Additionally, analytical expressions for current stress through the semiconductors and the DC-link capacitor are obtained for each converter under balanced and unbalanced load conditions. The lifetime analysis of the grid-forming converter indicates that the xyn-GFC has the lowest wear-out. Furthermore, this work highlights the influence of high-frequency components on the RMS current of the DC-link capacitor. The xyn-GFC demonstrates a lower probability of capacitor failure compared to the other converters, even with higher low-frequency components. A sensitivity analysis shows that the xyn-GFC can increase its output power in 12% or reduce its heatsink volume in 25% to achieve the same wear-out B10 lifetime as the abn-GFC (i.e., benchmark) under nominal conditions. An experiment is conducted using a full-bridge converter and discrete IGBTs to measure the power losses in the semiconductors and the case temperature of the IGBTs. Compared with the αβn-converter, the xyn-converter shows 44% lower power losses, and the abn-converter shows 18% lower power losses. Finally, the thermal stress analysis is validated by means of a 2Φ3W converter prototype with an open semiconductor module. For the evaluated converters, the xyn-GFC has the lowest thermal stress for balanced and unbalanced load conditions and therefore the longest lifetime. Experimental validation shows that the average temperature of the xyn-GFC is 19.4% and 23.3% lower than both the abn-GFC and the αβn-GFC under balanced load conditions.